2017
DOI: 10.14527/pegegog.2018.008
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of teacher candidates' epistemological beliefs: A qualitative study

Abstract: This study aimed to determine epistemological beliefs of teacher candidates. For this aim, semi-structured interviews were conducted with 56 teacher candidates. The interviews were recorded and records related to epistemological beliefs were transcribed, and then descriptive analyses were conducted. The results of the analyses revealed three main belief dimension. Regarding the first dimension, the candidates associated between learning and effort, and they thought that the innate ability would improve via eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…In particular, Schommer's (1990) conceptualization is built using an exploratory study in which the questionnaire construction has been reported accordingly. The instrument has been adopted in many fields, looking into specific epistemological beliefs on a particular knowledge theory (Aslan, 2017;Yıldırır and Çirkinoğlu-Şekercioğlu, 2018;Uzuriaga López, 2021). To this end, Schommer (1990) presupposes five epistemological dimensions, three of which relate to knowledge (i.e., structure, certainty, and source).…”
Section: Student's Epistemological Beliefsmentioning
confidence: 99%
“…In particular, Schommer's (1990) conceptualization is built using an exploratory study in which the questionnaire construction has been reported accordingly. The instrument has been adopted in many fields, looking into specific epistemological beliefs on a particular knowledge theory (Aslan, 2017;Yıldırır and Çirkinoğlu-Şekercioğlu, 2018;Uzuriaga López, 2021). To this end, Schommer (1990) presupposes five epistemological dimensions, three of which relate to knowledge (i.e., structure, certainty, and source).…”
Section: Student's Epistemological Beliefsmentioning
confidence: 99%
“…Cebirsel düşünme becerileri ile matematik odaklı epistemolojik inançların boyutları arasında farklı düzeylerde ilişkinin belirlenmiş olması, Schommer (1990) tarafından dile getirilen bilgilerin birbirinden bağımsız parçalardan ve boyutlardan oluştuğu kuramsal anlayışla da örtüşmektedir. Aynı zamanda bu bulgu, öğrencilerin çoğunluğunun öğrenmenin çabaya bağlı inançlarını ön planda tuttuğu ve bu yönde daha gelişmiş epistemolojik inançlara sahip olduğu söylemleri de desteklemektedir (Öngen, 2003;Yıldırır & Çirkinoğlu-Şekercioğlu, 2018).…”
Section: Tartışma Ve Sonuçunclassified